EFFECT OF LIQUIDITY, INVENTORY INTENSITY, LEVERAGE, AND CORPORATE SIZE ON TAX AGGRESSIVENESS ON PHARMACEUTICAL COMPANIES: PENGARUH LIKUIDITAS, INTENSITAS PERSEDIAAN, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN FARMASI - Maywanti Khoirunnisa; Yanti Budi Asih (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2021)
This research aims to determine whether there is an effect of liquidity, inventory intensity, leverage, and company size on tax aggressiveness in pharmaceutical companies listed on the Indonesian Stock Exchange in 2016-2020. Six pharmaceutical companies were selected as samples with purposive sampling technique. From the six samples, financial statement data was used as secondary research data collected by documentation technique. The research data obtained were analyzed using descriptive statistical analysis and classical assumption test. The results show that liquidity has no significant negative effect on tax aggressiveness. Meanwhile, inventory intensity has a positive and significant effect on tax aggressiveness. Leverage has a positive and significant effect between inventory intensity and tax aggressiveness. And for the effect of of liquidity, inventory intensity, and leverage on tax aggressiveness with firm size as a moderating variable, has a significant negative effect on tax aggressiveness